Experiences of indigenous people participating in the Tutorial Education Program group -Health Actions: Protagonism and resilience during the COVID-19 pandemic - Fernandes Luna, Willian; da Silva Ferreira, Ivanildo; da Silva Santos, Pedro Manuel; Martinha de Souza, Raniel; de Jesus, Joelson Antonio; Brazão Lopes, Claudiana; Lolli, Pedro Augusto (Guará Journal, 2023)
This experience report describes the activities carried out, during the COVID-19 pandemic, by young indigenous university students under the Tutorial Education Program (PET) of the Federal University of São Carlos. ´This PET group was created in 2010, composed exclusively of indigenous university students and develops teaching, research and extension activities. For the construction of the manuscript, the materials produced by the group during the years 2020 to 2022 were rescued, having been written by five indigenous university students and two professors. Five main activities were developed: Social Communication and Health of Indigenous Peoples; PodCast about experiences of Indigenous Peoples in Brazil; Meetings of Indigenous Knowledge; Videos about indigenous singularities; Conversation Circles on the Health of Indigenous Peoples. Two aspects are worth highlighting: the return of Petianos to their communities of origin created a direct communication channel with the places; the need for virtual action enabled people from all over the country to participate. The activities had indigenous protagonism and gave visibility to indigenous health issues at the university, as well as responding to the needs of communities, showing themselves as resilience strategies and responding creatively and assertively to the challenges of the COVID-19 pandemic.